Optimizing Business Management Strategies in the Social Media Era: Facing New Year Challenges with Digital-Based Excellence - Sutrisno, Sutrisno; Purnomo, Suseno Hadi; Purba, Jan Horas Veryady (ADMAN: Journal of Contemporary Administration and Management, 2023)
In the last few decades, the advancement of information technology, especially in the field of social media, has created a new paradigm in the business world. Social media has evolved beyond being merely a tool for social interaction; it has become an integral part of corporate business strategies. This shift has given rise to a dynamic, competitive, and constantly changing business environment. This research aims to provide practical guidance for corporate leaders in navigating the challenges of business in this digital era while leveraging the opportunities presented by social media to achieve sustainable competitive advantages. The study employs an in-depth literature review with qualitative analysis, spanning the years 2014 to 2023. The information sources for this literature review were sourced from Google Scholar to ensure the currency and accuracy of the accessed data. The study's findings indicate that in optimizing business management strategies in the social media era, critical factors such as customer interaction on digital platforms, operational changes, and corporate culture should be considered. By harnessing digital-based excellence, companies can explore new opportunities, enhance efficiency, and respond more rapidly to market changes. Strengthening online reputation, consumer data analysis, product innovation, online reputation risk management, internal transformation, team collaboration, and fostering an innovative culture are key elements in the concept of optimizing business management strategies in the social media era. The combination of these external and internal aspects establishes a solid foundation for long-term growth and success.